Comparative analysis of oligonucleotide primers for high-throughput screening of genes encoding adenylation domains of nonribosomal peptide synthetases in actinomycetes - Bakal, Tomas; Goo, Kian-Sim; Najmanova, Lucie; Plhackova, Kamila; Kadlcik, Stanislav; Ulanova, Dana (Antonie van Leeuwenhoek, 2015)
In the biosynthesis of diverse natural bioactive products the adenylation domains (ADs) of nonribosomal peptide synthetases select specific precursors from the cellular pool and activate them for further incorporation into the scaffold of the final compound. Therefore, the drug discovery programs employing PCR-based screening studies of microbial collections or metagenomic libraries often use AD-coding genes as markers of relevant biosynthetic gene clusters. However, due to significant sequence diversity of ADs, the conventional approach using only one primer pair in a single screening experiment could be insufficient for maximal coverage of AD abundance. In this study, the widely used primer pair A3F/A7R was compared with the newly designed aa194F/aa413R one by 454 pyrosequencing of two sets of actinomycete strains from highly dissimilar environments: subseafloor sediments and forest soil. Individually, none of the primer pairs was able to cover the overall diversity of ADs. However, due to slightly shifted specificity of the primer pairs, the total number and diversity of identified ADs were noticeably extended when both primer pairs were used in a single assay. Additionally, the efficiency of AD detection by different primer combinations was confirmed on the model of Salinispora tropica genomic DNA of known sequence.
Keywords: sekvence nukleotidů; polymerázová řetězová reakce; interakční proteinové domény a motivy; Peptide Synthases; Consensus Sequence; pozičně specifické skórovací matice; Soil Microbiology; DNA Primers; Position-Specific Scoring Matrices; rychlé screeningové testy; Protein Interaction Domains and Motifs; Actinobacteria; konsenzuální sekvence; High-Throughput Screening Assays; DNA primery; půdní mikrobiologie; Polymerase Chain Reaction; Base Sequence; peptidsynthasy